Guía para el desarrollo de la Psicomotricidad de los niños/as de 4 a 5 años a través del juego - Echeverria Alba, Rosa Beatriz (2015)
Fine motor occupies a very important place and is indispensable in the early life of infants This paper aims to help the boy and girl 4-5 years to develop fine motor skills appropriately in the Children's Centre "Little Explorers" so these activities will be useful when the child starts with literacy Through the survey of teachers and parents were able to demonstrate the need for a guide to the proper development of fine motor skills, because the children had difficulties when performing activities with their hands and digital calipers, why was I prioritize in preparing this work, in order to better orient teachers to help children the proper development of fine motor skills. During this process has been considered theoretical aspects, methods, techniques, strategies and resources that were used at the time of learning, fine psicomotrisidad consists of all activities carried him fine body parts of which must be developed so correct. The guide is easy to apply and consisting of creative and flexible to the needs of the child and child activities, so the teacher and parent can apply it without difficulty.